Innovation method and networking scheme of TD-LTE/LTE FDD capacity promotion - Deping XU; GLujing GEN; Ritao CHENG (Dianxin kexue)
At first,the existing LTE carrier bandwidth allocation scheme was analyzed.According to characteristics of the LTE spectrum bandwidth resources,a innovation method of capacity promotion was proposed,and the planning network carrier allocation scheme was introduced in detail.Finally,the feasibility of the scheme was confirmed through rigorous and scientific field test and analysis.